2019
DOI: 10.26434/chemrxiv.11401347.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis and Styrene Copolymerization of Novel Chloro and Fluoro Ring-Disubstituted Isopropyl Cyanophenylacrylates

Abstract: <p>Novel chloro and fluoro ring-disubstituted isopropyl 3-phenyl-2-cyanoacrylates, RPhCH=C(CN)CO<sub>2</sub>CH(CH<sub>3</sub>)<sub>2 </sub>(where R is 2-chloro-4-fluoro, 2-chloro-6-fluoro, 3-chloro-2-fluoro, 3-chloro-4-fluoro, 4-chloro-3-fluoro) were prepared and copolymerized with styrene. The acrylates were synthesized by the piperidine catalyzed Knoevenagel condensation of ring-disubstituted benzaldehydes and isopropyl cyanoacetate and characterized by CHN elemental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 19.4 and 40.1 mol% of OPCA is present in the copolymers prepared at ST/ OPCA = 3 (mol), which is indicative of relatively high reactivity of the OPCA monomers towards ST radical which is typical of ring-substituted OPCA [18][19][20][21][22][23][24][25][26]. Since OPCA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated OPCA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Opca Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 19.4 and 40.1 mol% of OPCA is present in the copolymers prepared at ST/ OPCA = 3 (mol), which is indicative of relatively high reactivity of the OPCA monomers towards ST radical which is typical of ring-substituted OPCA [18][19][20][21][22][23][24][25][26]. Since OPCA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated OPCA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Opca Copolymersmentioning
confidence: 99%
“…Thus, copolymerization of electrophylic TSE monomers having double bonds substituted with halo, cyano, and carbonyl groups and electron-rich monosubstituted ethylenes such as styrene, N-vinylcarbazole, and vinyl acetate [16][17][18] show a tendency toward the formation of alternating copolymers -thus suggesting a way of functionalization of commercial polymers via introduction of isolated monomer units in copolymers. Earlier we have reported synthesis and styrene copolymerization of a number of dichloro and difluoro ringsubstituted methyl [19][20][21], ethyl [22], propyl [23][24][25], isopropyl [26,27], butyl [28,29], isobutyl [30,31], and 2-methoxyethyl [32] PCAs.…”
Section: Introductionmentioning
confidence: 99%
“…3-Chloro-2-fluorophenyl propyl [1], isopropyl [2], isobutyl [3], and butyl [4] phenylcyanoacrylates (PCA) are synthesized and copolymerized with ethynyl benzene.…”
Section: Introductionmentioning
confidence: 99%
“…4-(trifluoromethyl)phenyl ethyl PCA is reported in C(sp 3 )-H functionalizations of light hydrocarbons using decatungstate photocatalysis [9]; in a study of kinetic isotope effects for various hydride transfer reactions [10]; in conjugate hydrocyanation of αcyanoacrylates using potassium hexacyanoferrate(II) as cyanating reagent [11]; in study of solid superbase derived from lanthanum-magnesium composite oxide and its catalytic performance in the Knoevenagel condensation under solvent-free condition [12]; in novel multicomponent reaction involving isoquinoline, allenoate and cyanoacrylates [13]; in construction of heterocycles via 1,4-dipolar cycloaddition of quinoline-DMAD zwitterion with various dipolarophiles [14]; in a novel three-component reaction of triphenylphosphine, DMAD, and electron-deficient styrenes: synthesis of cyclopentenyl phosphoranes [15], and in the multicomponent reaction of dimethoxycarbene, dimethyl butynedioate and electrophilic styrenes leading to synthesis of highly substituted cyclopentenone acetals [16]. 2,4, as well as its butyl PCA [18] were prepared and copolymerized with styrene, in addition to being involved in catalyst study of the Knoevenagel condensation [19]. 4-Hydroxy-3,5dimethoxyphenyl ethyl PCA is mentioned in synthesis of biologically potent heterocycles [20]; in study of main-chain and guest-host NLO polymers [21], whereas its isopropyl PCA was synthesized and copolymerized with ethenyl benzene [22].…”
Section: Introductionmentioning
confidence: 99%